Towards Establishing a New System as a Basis for the Intelligent Ship Captain’s Responsibility for Transporting Goods: Inductive Critical Analytical Study - Al Ali, Fahad; Abdul-Hay, Imad al-Din (Journal of Legal Sciences, 2026)
The research addressed a set of essential elements whose words were intertwined with analysis, criticism, comparison, and deduction from the title, which was "Towards establishing a new system as a basis for the responsibility of the intelligent ship captain for the transport of goods (a critical analytical study)." The main problem was represented by the search for legal solutions, whether in the UAE legislation or in the European Directive dated 5/9/2023, which is the focal point in this study to establish a new system for the responsibility of the intelligent ship captain in the transport of goods, for the damages caused by intelligent ships or self-driving ships to shippers, consignees, or third parties as a result of actions attributed to this intelligent captain.This issue has piqued the interest of legal scholars, leading to the emergence of numerous legal opinions, both for and against, regarding the establishment of a new system of liability for the actions of artificial intelligence. This system incorporates and discusses general principles within the context of our specific problem, resulting in attempts by legal scholars to establish a foundation for this liability. Consequently, two sub-issues have arisen from this main problem: First, can the intelligent pilot or shore captain who navigates intelligent or autonomous vessels be recognized as having legal personality? Second, should an alternative solution be sought first, such as the liability of the individual for their defective, manufactured, or programmed products, especially if the commands issued to the intelligent pilot by the manufacturer or programmer are logical and not erroneous, given that the liability arises without fault on the part of the owner or operator?The study concluded with several key findings, most notably that the captain of an autonomous vessel will face both legal and technical challenges, whether operating on shore or aboard (in which case, the captain would be a robot). These challenges will all impact the captain's liability. Furthermore, establishing a legal framework for the liability of an intelligent ship's captain necessitates a specific system, initially grounding liability in the theory of human agency before ultimately granting legal personality to artificial intelligence.The study concluded with several recommendations, most notably urging the UAE legislature to enact legal provisions clarifying the legal basis for the liability of the captain of an autonomous vessel, given its unique characteristics and the inherent risks of maritime transport. Finally, the study emphasized the necessity for the UAE legislature, as well as the International Maritime Organization (IMO), to establish a specific legal framework for autonomous or smart vessels. This could be achieved either by amending the UAE Maritime Law or relevant international conventions to include explicit provisions addressing these vessels, or by developing a comprehensive legal system specifically for them.